2003
DOI: 10.1159/000067797
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside-Induced Reversible Tubular Dysfunction

Abstract: Nonoliguric renal insufficiency is a well-known nephrotoxic consequence of aminoglycosides, although reversible tubular damage in the absence of any change in the renal function has been occasionally found. Reported herein are 2 representative cases of a reversible tubular damage due to prolonged aminoglycoside administration: a patient with a Fanconi-like syndrome of proximal tubular dysfunction and a patient with a syndrome of hypokalemic metabolic alkalosis associated with hypomagnesemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
(35 reference statements)
1
25
0
2
Order By: Relevance
“…Gentamicin can interfere with specific transport mechanisms in the primal tubular system or can induce RFS. Usually, aminoglycoside-induced RFS is seen in patients with impaired renal function, but some reports of patients with normal kidney function exist [143]. Gentamicin enters the cell through the megalin-cubulin system [41].…”
Section: Aminoglycosides and Tetracyclinesmentioning
confidence: 99%
“…Gentamicin can interfere with specific transport mechanisms in the primal tubular system or can induce RFS. Usually, aminoglycoside-induced RFS is seen in patients with impaired renal function, but some reports of patients with normal kidney function exist [143]. Gentamicin enters the cell through the megalin-cubulin system [41].…”
Section: Aminoglycosides and Tetracyclinesmentioning
confidence: 99%
“…It is also associated with a decrease in urinary concentration along with increased excretion of sodium [1] . We have shown that a gentamicin (GM)-induced urinary concentration defect may in part be accounted for by a reduced abundance of aquaporin water channels in the kidney [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Hypomagnesemia is often found in the patients with renal failure [Kelepouris and Agus, 1998;Alexandridis et al, 2003]. Magnesium deficiency enhances drug-induced nephrotoxicity [Lajer et al, kinases (CDKs) at different phases of the cell cycle [Draetta, 1990;Sherr, 1994;Jung et al, 2010].…”
mentioning
confidence: 99%